DAMPAK REGULASI PAJAK TERHADAP PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) DALAM TRANSAKSI LINTAS NEGARA - Aida Dian Rami (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The use of QRIS as a cross-border payment method is rapidly expanding, enabling faster and more efficient transactions while reducing reliance on cash and credit cards. However, despite its convenience, taxation issues in international QRIS transactions remain a subject of debate, particularly concerning potential double taxation, hidden fees, and tax avoidance risks. In terms of value-added tax (VAT), there is still ambiguity regarding whether taxes should be imposed in the country of origin, the destination country, or both. Additionally, QRIS may create loopholes for tax avoidance on imported goods, allowing consumers to conduct direct transactions without going through proper customs duty mechanisms. From a consumer protection perspective, it is essential to evaluate the transparency of tax deductions in QRIS transactions and the dispute resolution mechanisms available in case of incorrect tax charges. Case studies from countries that have adopted QRIS, such as Singapore and Malaysia, serve as key references in understanding how fiscal regulations govern digital cross-border transactions. This article explores the legal and policy challenges that must be addressed to ensure QRIS operates optimally without disadvantaging consumers. Furthermore, it provides recommendations to establish a fairer and more transparent taxation framework for digital payments.